Risk of perimetric blindness among juvenile glaucoma patients. (9th February 2015) - Gupta, Viney; Devi K, Saranya; Kumar, Sandip; Pandey, Ravindra Mohan; Sihota, Ramanjit; Sharma, Ajay; Gupta, Shikha
Abstract Aim To estimate rates of progression and to asssess the projected lifetime risk of blindness among treated eyes of juvenile‐onset primary open glaucoma (JOAG) patients. Methods Rates of change of the visual field index of JOAG patients (diagnosed between the age of 10–40 years), with at least 5 year follow up, were used to estimate the lifetime risk of perimetric blindness. Both the eyes of patients were included in the analysis wherever possible. Average life expectancy of the population was used to calculate the lifetime risk of perimetric blindness. A regression analysis of factors contributing to faster rates of progression was performed. Results One hundred and two eyes of 54 patients were included in the study. Mean age at the time of baseline visual field was 26.6 ± 9.8 years (15–40 years). The average visual field index change per year was −0.9% (range −6.4 to +2.0% per year) and 18 eyes (17%) showed a progression greater than −2% per year. The cumulative risk of an eye losing 50% and 100% of its visual field index was 30% and 22% respectively over the patients' lifetime. The projected risk of bilateral blindness among JOAG patients over their lifetime was 10%. Long term IOP fluctuation was significantly associated with faster rates of progression (Odds ratio = 2.74; p = 0.012). Conclusions Though the rate of visual field deterioration with treatment, among juvenile glaucoma patients is lower compared to that among other types of primary glaucoma, the projected lifetime risk of perimetric blindness in these eyes is similar, despite the longer duration of disease in this age group.